1987
DOI: 10.1111/j.1439-0434.1987.tb04386.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Geminivirus Causing Yellow Mosaic Disease of Horsegram (Macrotyloma uniflorum [Lam.] Verdc.) in India*

Abstract: Horsegram yellow mosaic disease was shown to be caused by a geminivirus; horsegram yellow mosaic virus (HYMV). The virus could not be transmitted by mechanical sap inoculation. Leaf dip and purified virus preparations showed geminate virus particles, measuring 15‐18 * 30 nm. An antiserum for HYMV was produced and in enzyme‐linked immunosorbent assay (ELISA) and immunosorbent electron microscopy (ISEM) tests HYMV was detected in leaf extracts of fieldinfected bambara groundnut, french bean, groundnut, limabean,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Isolation, purification, electron microscopic and serological studies of HgYMV have been reported (Muniyappa et al 1987). However, the present study is the first report of the molecular characterization of the genome components of HgYMV.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Isolation, purification, electron microscopic and serological studies of HgYMV have been reported (Muniyappa et al 1987). However, the present study is the first report of the molecular characterization of the genome components of HgYMV.…”
Section: Introductionmentioning
confidence: 72%
“…Later preliminary electron microscopic studies revealed geminate particles (Muniyappa et al 1987) from the infected leaves. Swanson et al (1992) showed that monoclonal antibodies raised against African cassava mosaic virus It had been established that ori is a hot-spot for recombination (Stanley 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Virus purification: IGMV was purified from infected cassava or N. benthamiana leaves using a method described by GOODMAN et al (1977) and MUNIYAPPA et al (1987) with some modifications. Leaves from N. benthamiana were harvested 12-15 days after inoculation and homogenized in 0.1 M sodium phosphate buffer, pH 7.8 (2 ml/g) containing 1 % 2-mercaptoethanol, 0.001 M cysteine hydrochloride, 0.01 M sodium EDTA and chloroform (1 ml/g).…”
Section: Methodsmentioning
confidence: 99%
“…YMD was characterized by yellow mosaic on leaves, coupled with reduction of leaf size and plant height in severely infected plants. This virus was initially identified as HgYMV (Muniyappa, Rajeshwari, Bharathan, Reddy, & Nolt, 1987). In addition to horse gram, HgYMV infects French bean, groundnut, lima bean, mungbean, pigeonpea, soybean and bambara groundnut in India.…”
Section: Horse Grammentioning
confidence: 99%